Comprehensive analysis of Perilla frutescens (L.) Britt. along the value chain in northeast Inner Mongolia - Yuan Chen; Hui Niu; Lingling Fan; Chunxiu Wen; Xinxin Wei; Zeyuan Zhao; Seesregdorj Surenjidiin; Aruhan; Minhui Li (Science of Traditional Chinese Medicine)
Abstract. Objective. To ensure the quality of Perilla frutescens (L.) Britt. and improve the associated benefits for stakeholders, this study analyzed the influences of different circulation channels and stakeholders on the quality, price, and other factors of P. frutescens with consideration to P. frutescens distribution. Method. We interviewed the local stakeholders and e-commerce platforms in Oroqen Autonomous Banner and Morin Dawa Daur Autonomous Banner regarding the origin, circulation, distribution, and prices of different medicinal parts of P. frutescens. In addition, the maximum entropy model was used to predict the potential distribution of P. frutescens in the study area. According to the Chinese Pharmacopeia (2020 edition), we measured the content of index components in the collected Perillae Folium, Perillae Caulis, and Perillae Fructus samples and evaluated the quality of the samples by quantitative and cluster analyses. Remote sensing was employed to distinguish and calculate the P. frutescens area in highly suitable regions. The autoregressive integrated moving average model was adopted to analyze the Perillae Fructus price in the study area. Result. The results showed 8 value chains for P. frutescens. The cooperation chain between farmers and enterprises in the study area could maximize the benefits for all stakeholders and guarantee the quality of the medicinal materials. The results of the regionalization analysis showed that the most suitable area for planting P. frutescens was the junction between Oroqen Autonomous Banner and Morin Dawa Daur Autonomous Banner. Chemical results showed that Perillae Fructus and Perillae Caulis samples were unqualified and mostly purchased from e-commerce platforms. We identified 5 land types, among which the cultivated land area was 3247.7501 km2. The price of Perillae Fructus in the study area showed a rising trend, although this trend slowed down. Conclusion. This study involved various links in the production and circulation of medicinal materials from planting to consumption by consumers, which can help to facilitate the future research on any link. The findings help to guarantee the quality of medicinal materials and benefits of all stakeholders and promote the development of the P. frutescens industry in the study area.